Fine Motor Analysis of Infants Aged 7-12 Months Based on Breast Milk - Indah Rahmadaniah; Marchatus Soleha; Rini Anggeriani (International Journal of Health Science and Technology, 2021)
This study aims to produce new scientific information about the fine motor skills of breastfed infants. Method: The type of research is an analytic survey. The population, all infants aged 7-12 months as many as 57 babies, the sample was taken by purposive sampling as many as 47 respondents, the data was taken through a survey using Google forms. Data analysis using chi-square statistical test. Result: obtained p-value = 0,058. In conclusion, there is no significant relationship between breastfeeding and fine motor skills in infants aged 7-12 months.